Explaining the comparative perception of e-payment: role of e-shopping value, e-payment benefits and Islamic compliance - Garrouch, Karim F. (Journal of Islamic marketing, 2022)
Purpose This study aims to examine three factors affecting the comparative e-payment perception, namely, perceived e-shopping value, e-payment benefits and Islamic Sharia compliance. It verifies an original model explaining the comparative perception of e-payment as a tool to pay online purchases. The newly integrated variables are the perceived compliance of the e-payment with Islamic Sharia, as a moderator, and the perceived e-shopping value, as a predictor. This investigation also tested the mediating role of e-payment benefits between perceived e-shopping value and e-payment comparative perception. Design/methodology/approach A questionnaire was distributed, via an online survey, to professional and personal networks of Master students who have spread the survey link to their social media groups. This procedure resulted in 185 valid observations. Findings Results show that the comparative perception of e-payment systems, as opposed to cash on delivery, is explained directly by e-payment benefits and indirectly by e-shopping value. The comparison of the model paths based on the perceived compliance to Islamic Sharia showed that this variable is non-significant as a moderator. Originality/value The verified model and paths of this study have not been covered yet, namely, the direct and indirect effects of e-shopping value. Thus, their verification constitutes the main originality of this article. Besides, the verification of the moderating role of compliance to Islamic sharia has not been verified in prior studies about e-payment.